Octenol as Attractant to Nyssomyia neivai (Diptera: Psychodidae: Phlebotominae) in the Field - Pinto, Mara Cristina [UNESP]; Barbieri, K. [UNESP]; Silva, M. C. E. [UNESP]; Graminha, Márcia Aparecida Silva [UNESP]; Casanova, C.; Andrade, A. J.; Eiras, A. E. (Entomological Soc Amer, 2011)
The kairomone octenol is known as attractive to hematophagous Diptera such as mosquitoes, tsetse flies, and midges. There is little evidence that traps baited with octenol are also effective in attracting phlebotomine sand flies. The present report evaluated octenol in modified Centers for Disease Control and Prevention (CDC) traps in two experiments: 1) modified CDC trap without light and 2) modified CDC trap with light. The traps were baited with octenol at concentrations of 0.5, 27, and 43 mg/h in Rifled() locality, São Paulo, Brazil. Traps without octenol were used as controls. The sand fly Nyssomyia neivai (Pinto) (=Lutzomyia neivai) (Diptera: Psychodidae: Phlebotominae) was the prevalent species (99.9%) in both experiments. The results of the experiments showed that traps baited with octenol at 27 and 43 mg/h caught significantly more N. neivai than control and octenol at 0.5 mg/h with and without light. This is the first report that shows that octenol itself is attractive to N. neivai and associated with light traps significantly increases the catches.
Keywords: Nyssomyia neivai; octenol; kairomones; attractiveness; sand flies